2018
DOI: 10.21037/tau.2018.09.12
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using a novel non-invasive ambulatory tibial nerve stimulation device for the home-based treatment of overactive bladder symptoms

Abstract: BackgroundTo evaluate safety, acceptability and pilot efficacy of transcutaneous low-frequency tibial nerve stimulation (TNS) using a novel device as home-based neuromodulation.MethodsIn this single-centre pilot study, 48 patients with overactive bladder (OAB) (24 with neurogenic and 24 with idiopathic OAB) were randomized to use a self-applicating ambulatory skin-adhering device stimulating transcutaneously the tibial nerve at 1 Hz for 30 minutes, either once daily or once weekly, for 12 weeks. Changes in OAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…Finally, 19 studies [ 3 , 4 , 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included. Of these, nine were experimental [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], including eight RTCs [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 24 ] ( Table 2 ); four were observational studies [ 5 , 25 , 26 , 27 ] ( Table 3 ), and six were either systematic reviews [ 4 , 29 , 31 ] or a meta-analysis [ 28 ], while two encompassed both types of studies [ 30 , 32 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 19 studies [ 3 , 4 , 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included. Of these, nine were experimental [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], including eight RTCs [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 24 ] ( Table 2 ); four were observational studies [ 5 , 25 , 26 , 27 ] ( Table 3 ), and six were either systematic reviews [ 4 , 29 , 31 ] or a meta-analysis [ 28 ], while two encompassed both types of studies [ 30 , 32 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrasting daily or weekly treatment [ 21 ] with TTNS, 100% of weekly participants completed the compliance and experience questionnaire, in comparison to 90.5% of patients on daily therapy [ 21 ]. Although 53% (18) gave as a result a moderate or significant improvement in symptoms for the global response assessment (GRA), 75% (13/20) of neurological patients with OAB and 36% (5/14) of patients with idiopathic OAB responded to the intervention [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported efficacy of TTNS on OAB patients. [21][22][23] While others have shown TTNS to compare favorably to medications, 24 Ramírez-García et al demonstrated non-inferiority between transcutaneous and percutaneous tibial nerve stimulation. 25 Another study by Martin-Garcia, et al 26 that compared PTNS to a home-based stimulation system found no statistically significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature revealed few studies investigating TTNS among neurogenic bladder (Amarenco et al, 2003;Monteiro et al, 2014;Perissinotto et al, 2015;Valles-Antuna et al, 2017). Specific to people with MS, two experimental studies were identified (de Seze et al, 2011;Seth et al, 2018). In the uncontrolled experimental study by de Seze et al (2011), the authors recruited 70 people with MS and OAB.…”
Section: Introductionmentioning
confidence: 99%
“…The study compared two different protocol of TTNS 30 min daily vs. 30 min weekly, for 12 weeks between 24 MS participants with OAB to 24 participants with idiopathic OAB. TTNS was shown to be safe, acceptable and significant improvements in urinary symptoms including OAB were reported for both groups ( Seth et al ., 2015 ; Seth et al ., 2018 ). The electrical stimulation parameters for both groups were at 27 mA current, with 1 Hz current frequency and pulse width was between 70 and 560 µs and was consecutively increased depending upon the maximum tolerable sensory and best sensory-motor response.…”
Section: Introductionmentioning
confidence: 99%